The Role of ICT in Reducing Information Asymmetry for Financial Access - Simplice Asongu; Bertrand Moulin (African Governance and Development Institute (AGDI), 2016)
This study assesses the role of ICT in complementing private credit bureaus (PCB) and public credit registries (PCR) in reducing information asymmetry for financial access. The empirical evidence is based on Generalised Method of Moments with 53 African countries for the period 2004-2011. The following findings are established. First on financial access: (i) the marginal effects from interactions between ICT and PCR (PCB) are consistently positive (negative); (ii) net effects from interactions are negative with the higher magnitude from PCR and (iii) only thresholds corresponding to interactions between PCR and internet penetration are within range. Second, findings on financial allocation efficiency reveal positive marginal and net effects exclusively for mobile phones and PCR. Third, allocation efficiency may be constrained by increasing financial deposits. Overall, the complementarity between information offices and ICT in boosting financial access is still very limited. Policy implications are discussed with emphasis on improving the engaged complementarity and fighting surplus liquidity.
Keywords: G20; G29; L96; O40; O55; 330; Financial access; Information asymmetry; ICT